2019
DOI: 10.22271/ortho.2019.v5.i1a.06
|View full text |Cite
|
Sign up to set email alerts
|

Comparing results of Endoscopic microdiscectomy and conventional discectomy for lumbar disc disease: A short term study

Abstract: Introduction: Chronic lumbo-sacral pain is a common and challenging clinical entity in pain management centre. The most commonly involved surgical indication are intractable leg or back pain and significant functional impairment that have been unresponsive to conservative measures. This is a level 2 evidence study where we have studied results of endoscopic discectomy and compared it to conventional discectomy procedure. Material and Methods: We selected 40 patients with severe low back pain radiating to one o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…In addition, Dvorak et al [20] report that 70% of patients suffered low back pain during long-term follow-up after open lumbar discectomy. Vora et al [21] reported that average operative time for endoscopic discectomy was higher than conventional discectomy. However, there was minimal blood loss compared to conventional discectomy.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Dvorak et al [20] report that 70% of patients suffered low back pain during long-term follow-up after open lumbar discectomy. Vora et al [21] reported that average operative time for endoscopic discectomy was higher than conventional discectomy. However, there was minimal blood loss compared to conventional discectomy.…”
Section: Discussionmentioning
confidence: 99%